Distance learning during one month (February, 24 – March, 25) of 2019-2022 years during Covid-19 period and war of russia with Ukraine - Antypenko, L.; Antypenko, O. M.; Антипенко, Олексій Миколайович (My University, 2022)
The COVID-19 pandemic, is an ongoing global pandemic of coronavirus disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [1]. The World Health Organization (WHO) declared a Public Health Emergency of International Concern on 30 January 2020 and a pandemic on 11 March 2020.